2013
DOI: 10.1371/journal.pone.0055535
|View full text |Cite
|
Sign up to set email alerts
|

VOC Contamination in Hospital, from Stationary Sampling of a Large Panel of Compounds, in View of Healthcare Workers and Patients Exposure Assessment

Abstract: BackgroundWe aimed to assess, for the first time, the nature of the indoor air contamination of hospitals.Methods and FindingsMore than 40 volatile organic compounds (VOCs) including aliphatic, aromatic and halogenated hydrocarbons, aldehydes, alcohols, ketones, ethers and terpenes were measured in a teaching hospital in France, from sampling in six sampling sites – reception hall, patient room, nursing care, post-anesthesia care unit, parasitology-mycology laboratory and flexible endoscope disinfection unit –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
53
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 35 publications
8
53
2
Order By: Relevance
“…Indoor TVOC concentrations were observed to be in a similar range as reported in other studies in healthcare centers [20,21]. In a previous hospital-based study similar concentrations of alcohols were observed at around 1000 μg/m 3 for ethanol and 100 μg/m 3 for isopropanol [20,22]. Acetone levels were all below the 95th percentile of 30.6 μg/m 3 , as earlier reported for indoor air of public buildings [5].…”
Section: Discussionsupporting
confidence: 82%
“…Indoor TVOC concentrations were observed to be in a similar range as reported in other studies in healthcare centers [20,21]. In a previous hospital-based study similar concentrations of alcohols were observed at around 1000 μg/m 3 for ethanol and 100 μg/m 3 for isopropanol [20,22]. Acetone levels were all below the 95th percentile of 30.6 μg/m 3 , as earlier reported for indoor air of public buildings [5].…”
Section: Discussionsupporting
confidence: 82%
“…Exposure levels were higher for some VOCs such as ethanol, and lower with multiple measurements below the LOD for VOCs such as methyl methacrylates. Comparable exposure data were reported in a study of VOC exposures in six locations at a hospital in France35 where the highest mean exposure levels were for ethanol (928 µg/m 3 ) and isopropanol (48 µg/m 3 ). They measured the highest alcohol concentrations in postanaesthesia care, nursing care and the hospital room.…”
Section: Discussionsupporting
confidence: 53%
“…Cleaning staff are often exposed to a complex mixture of irritants and sensitizers (Bessonneau et al , 2013; Gonzalez et al , 2014; Melchior Gerster et al , 2014). Exposure to cleaning agents with sporicidal activity such as glutaraldehyde, formaldehyde, and chlorine compounds is associated with adverse health outcomes which include upper airway irritation and irritant or sensitizer induced asthma (AOEC, 2015).…”
Section: Discussionmentioning
confidence: 99%